2023
DOI: 10.1029/2022jc019459
|View full text |Cite
|
Sign up to set email alerts
|

Fast Ice Thickness Distribution in the Western Ross Sea in Late Spring

Abstract: We present a 700 km airborne electromagnetic survey of late‐spring fast ice and sub‐ice platelet layer (SIPL) thickness distributions from McMurdo Sound to Cape Adare, providing a first‐time inventory of fast ice thickness close to its annual maximum. The overall mode of the consolidated ice (including snow) thickness was 1.9 m, less than its mean of 2.6 ± 1.0 m. Our survey was partitioned into level and rough ice, and SIPL thickness was estimated under level ice. Although level ice, with a mode of 2.0 m and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 93 publications
2
9
0
Order By: Relevance
“…Giles et al (2008) estimate using remote sensing that 33% of the area of East Antarctic fast ice in 1997-1999 was rough, indicating that deformation is a major determinant of overall fast-ice volume (assuming their estimated values of 1.7 and 5.0 m for smooth and rough fast ice, respectively), and providing strong rationale for studies of rough fast ice to be prioritized. Recently Langhorne et al (2023) confirmed the pervasiveness of deformed fast ice in the western Ross Sea where rough ice occupied 50% of the volume of a 700 km airborne electromagnetic (AEM) thickness transect. The rough ice had a modal thickness of 3.3 m, while the level ice was 2.0 m. Near Inexpressible Island in the Ross Sea (163.7°E, 74.9°S), the dynamic formation of rough fast ice up to 3-4 m thick was observed after pack ice was blown into a small bay after almost 3 days of persistent onshore winds (Zhai et al, 2019).…”
Section: Dynamic Thickness Redistribution: the Formation Of Rough Fas...mentioning
confidence: 90%
See 2 more Smart Citations
“…Giles et al (2008) estimate using remote sensing that 33% of the area of East Antarctic fast ice in 1997-1999 was rough, indicating that deformation is a major determinant of overall fast-ice volume (assuming their estimated values of 1.7 and 5.0 m for smooth and rough fast ice, respectively), and providing strong rationale for studies of rough fast ice to be prioritized. Recently Langhorne et al (2023) confirmed the pervasiveness of deformed fast ice in the western Ross Sea where rough ice occupied 50% of the volume of a 700 km airborne electromagnetic (AEM) thickness transect. The rough ice had a modal thickness of 3.3 m, while the level ice was 2.0 m. Near Inexpressible Island in the Ross Sea (163.7°E, 74.9°S), the dynamic formation of rough fast ice up to 3-4 m thick was observed after pack ice was blown into a small bay after almost 3 days of persistent onshore winds (Zhai et al, 2019).…”
Section: Dynamic Thickness Redistribution: the Formation Of Rough Fas...mentioning
confidence: 90%
“…Recently Langhorne et al. (2023) confirmed the pervasiveness of deformed fast ice in the western Ross Sea where rough ice occupied 50% of the volume of a 700 km airborne electromagnetic (AEM) thickness transect. The rough ice had a modal thickness of 3.3 m, while the level ice was 2.0 m. Near Inexpressible Island in the Ross Sea (163.7°E, 74.9°S), the dynamic formation of rough fast ice up to 3–4 m thick was observed after pack ice was blown into a small bay after almost 3 days of persistent onshore winds (Zhai et al., 2019).…”
Section: Fast‐ice Growth Properties and Seasonalitymentioning
confidence: 98%
See 1 more Smart Citation
“…In north Terra Nova Bay, marine ice (Souchez et al, 1995) and basal freezing (Han and Lee, 2015) occur beneath the Campbell Ice Tongue (Figure 1). Beneath adjoining fast ice, a SIPL was detected in biological studies in late spring of 2002, 2005, and 2006(Vacchi et al, 2004 and in AEM surveys in late spring of 2017 (Langhorne et al, 2023). The presence of marine ice and SIPL signal that in situ supercooled ISW is circulating in the region, which the AEM surveys indicated could be locally sourced from the ice tongue (Langhorne et al, 2023).…”
Section: Introductionmentioning
confidence: 95%
“…South of the Drygalski Ice Tongue, platelet ice was observed in a sea ice core (Jeffries and Weeks, 1993) and beneath fast ice (Stevens et al, 2017). The edge of Hells Gate Ice Shelf is comprised entirely of marine ice (Souchez et al, 1991), with thick frazil and platelet ice layers observed beneath the ice shelf (Tison et al, 1993, Souchez et al, 1991, and adjoining fast ice (Langhorne et al, 2023;Tison et al, 1998). An extensive airborne electromagnetic induction (AEM) survey of fast ice along the Victoria Land Coastline identified that smaller ice bodies including ice tongues and marine-manuscript submitted to Journal of Geophysical Research: Oceans terminating outlet glaciers also contribute to the formation of in situ supercooled ISW and platelet ice in the western Ross Sea (Langhorne et al, 2023).…”
Section: Introductionmentioning
confidence: 99%